Conceptualizing Pornographication: A Lack of Clarity and Problems for Feminist Analysis - Tyler, Meagan; Quek, Kaye (Sexualization, Media, & Society, 2016)
The mainstreaming of pornography, often referred to as pornographication, pornification, or porn-chic, has become a topic of considerable academic and popular interest. In the last 15 years, an expanding academic literature has documented and begun to analyze the increasing consumption and normalization of pornography as well as pornographic imagery. More recently, there has also been a growing concern among policymakers and commentators in the mainstream media about trends labeled “sexualization” and, in particular, the potential consequences of these trends for children. This article begins by sketching out the academic origins of “pornographication” and related terms before considering the different ways that prominent authors have conceptualized them. Recent literature on sexualization is then outlined, with a focus on understanding this in the context of discussions around pornographication. Using a number of examples from key academic texts, and from prominent print media outlets in Australia, we argue that there is a lack of conceptual clarity about pornographication and that pornographication is often conflated with sexualization. We suggest that the lack of clarity in existing literature creates two key issues for feminist analysis: (1) it obscures the role of the pornography industry in the processes of pornographication and (2) it deflects discussion away from the potential harms of the normalization of pornography and pornographic imagery for adult women. It is, therefore, important to clarify and separate the terminology of pornographication and sexualization in order to further critical feminist analyses of these cultural trends.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; cours; discipline; discours dominant; pornographie; premier cycle; périodes historiques; sciences humaines; sciences sociales; sex1911; sexualité; systèmes d'oppressions; thématiques; violences

Mon corps a-t-il un sexe? Sur le genre, dialogues entre biologies et sciences sociales - Gonthier, Josiane; Ruppli-Coursange, Mireille (La Découverte, 2015)
"Sexe" est l'un des mots de la langue française que les gens sans distinction de classe, de religion, d'apparence ou de profession, utilisent avec grand intérêt, qu'ils soient accoudés au zinc d'un bistrot ou à la paillasse d'un laboratoire de biologie moléculaire. Deux mises en scène distinctes, sociale ou scientifique ; deux scénarios différents : d'un côté, les histoires d'amour ou d'imaginaire sexuel, de l'autre, les recherches biologiques. Sous ce mot de "sexe", notre langue, si riche, produit une polysémie bien fâcheuse. L'ambition de ce volume, qui rassemble les contributions de chercheurs et chercheuses en sciences de la vie et en sciences humaines et sociales est de faire le point sur les connaissances concernant le sexe biologique et ses variations, dont on sait désormais qu'il ne permet pas de séparer les individus en deux catégories bien distinctes. Ce livre veut aussi évaluer l'impact du genre sur le développement du corps des êtres sexués et sur la construction de leur identité. Enfin, il cherche à apprécier dans quelle mesure les croyances liées au genre (bicatégorisation mâle-femelle stricte, supériorité masculine) ont pu influencer les recherches menées sur le sexe biologique. Et les témoignages de personnes intersexes et transgenres apportent sur la question de l'identité sexuée un éclairage complémentaire qui bouscule les "réponses" que donnent le plus souvent la médecine et le droit.
Section: 1 vol. (358 p. - [32] p. de pl.) : ill. en noir et en coul. ; 24 cm.
Keywords: approches et analyses; biologie; corps; cours; discipline; discours dominant; premier cycle; psy4910; psychologie; pédagogie; queer; sciences; sciences humaines; sciences sociales; sexualité; systèmes d'oppressions; thématiques; épistémologie; études de genres

Conférence «La construction de la légitimité intellectuelle des femmes» - Charron, Hélène (2014)
Conférence d'ouverture du colloque « Les femmes dans les sciences humaines : étudier, enseigner, travailler, militer » Date de l’événement : 20 mars 2014 Hélène Charron, chercheure au Conseil du statut de la femme, chercheure associée à la Chaire Claire-Bonenfant de l’Université Laval, et chargée de cours en études féministes et en sociologie.
Keywords: approches et analyses; discipline; discours dominant; genre; histoire et politique; identités LGBTQIA2+; milieux universitaires; sciences; sciences humaines; sciences sociales; sociologie; systèmes d'oppressions; thématiques